Primary intrathymic lymphangioma in an infant - Channabasavaraj S Hiremath; Utkarsh Sanghavi; Aditya N Doddamane; Anuradha Kamath; Shekhar Rao (Wolters Kluwer Medknow Publications, 2020)
Lymphangiomas are relatively uncommon lesions of the lymphatic channels which can arise in virtually any part of the body. Although the most common site is the head/neck region, they could be found in the mediastinum. If mediastinal lymphangiomas are said to be rare, the thymic subentity is even scanty. We describe one case of mediastinal lymphangioma with a true intrathymic localization, which to our knowledge has been reported just once in the literature. This case report elucidates the surgical management of the first lymphangioma reported in an infant.